(3GdGTJQGcGJ ceUOQ dJehjd GdJCejfGJ GdGLJeGYjI (B: s (3OQGSI JMdjdjI ebGQfI (B/ s - (3EHQGgje jhSa eMeO GdHjWGQs; (3CMeO MSf GdHQYj s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2013)
(3gfGdc YOI GJLGgGJ GdabgjI HTCf JMOjO ef jSge aj Jehjd GdJCejfGJ GdGLJeGYjI ef NdGd GdGTJQGcGJ(B: (3h dbO MSe GdJWHjb GdYedj GdNdGa Gdabgj HETQGc GdLejY (B- (3GdYGed h UGMH GdYed h GdOhdI (B- (3aj GdJehjd ef NdGd GdGTJQGcGJ aj CZdH GdfXe(B. (3h dbO CbQ GdeTQY GdCQOfj aj bGfhf GdVeGf GdGLJeGYj(B: (3eSGgeI GdYeGd h CUMGH GdCYeGd h CYai GdOhdI(B: (3CeG GdeTQY GdeUQj adbO CbQ aj bGfhf GdJCejf GdGLJeGYj eSGgeI GdYeGd h CUMGH GdCYeGd h GdOhdI(B: (3CeG GdeTQY GdHQjWGfj(B: (3aehd GdJCejfGJ GdGLJeGYj (B( (3GdGLJeGYjI (B) (3HeRjL ef GdGTJQGcGJ h GdVQGFH GdNGUI h GdOYe ef GdNRGfI GdYGeI(B: (3h GdGTJQGcGJ jDOjgG GdYGed h UGMH GdYed h GdYGedhf dMSGHge GdNGUs
(3jTJed Ydi edGMb(B: (3UaMGJ (B736-777s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdJTQjYGJ GdGLJeGYjI, (B2013s
(3HHdjhLQGajG(B: (3UaMGJ (B704-735s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdJTQjYGJ GdELJeGYjIs; (3GdGTJQGcGJs; (3GdJCejfGJ GdGLJeGYjIs; (3GdJehjds; (3GdbGfhf GdGfLdjRis; (3Jehjd GdGTJQGcGJs; (3WHjYI GdGTJQGcGJs; (3JMOjO GdGTJQGcGJs; (3GdGTJQGcGJ hGSJMbGb GdCLQs; (3JMUjd GdGTJQGcGJs; (3VeGfGJ JMUjd GdGTJQGcGJs; (3GdeNGdaGJ GdeQJHWI HGdGTJQGcGJs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdJTQjYGJ GdELJeGYjIs